Nutrient smuggling: Commensal gut bacteria‐derived extracellular vesicles scavenge vitamin B12 and related cobamides for microbe and host acquisition. Issue 10 (11th October 2022) - Juodeikis, Rokas; Jones, Emily; Deery, Evelyne; Beal, David M.; Stentz, Régis; Kräutler, Bernhard; Carding, Simon R.; Warren, Martin J.
Abstract: The processes by which bacteria proactively scavenge essential nutrients in crowded environments such as the gastrointestinal tract are not fully understood. In this context, we observed that bacterial extracellular vesicles (BEVs) produced by the human commensal gut microbe Bacteroides thetaiotaomicron contain multiple high‐affinity vitamin B12 binding proteins suggesting that the vesicles play a role in micronutrient scavenging. Vitamin B12 belongs to the cobamide family of cofactors that regulate microbial communities through their limited bioavailability. We show that B. thetaiotaomicron derived BEVs bind a variety of cobamides and not only deliver them back to the parental bacterium but also sequester the micronutrient from competing bacteria. Additionally, Caco‐2 cells, representing a model intestinal epithelial barrier, acquire cobamide‐bound vesicles and traffic them to lysosomes, thereby mimicking the physiological cobalamin‐specific intrinsic factor‐mediated uptake process. Our findings identify a novel cobamide binding activity associated with BEVs with far‐reaching implications for microbiota and host health.